Diversification options in rice-based systems in Côte d'Ivoire - Yeo, Y.S-A.; Dossou-Yovo, Elliott Ronald (Africa Rice Center, 2023)
The study aimed to evaluate the impact of crop establishment, residue management, and diversification on grain yield, and profitability lowland rice systems in Côte d'Ivoire. Over the period from 2021 to 2023, eight agricultural practices were examined, including rice cultivated once a year under transplanting (T1), rice cultivated twice a year under transplanting (T2), rice cultivated three times a year under transplanting (T3), rice-bean rotation under transplanting (T4), rice-rice-bean rotation under transplanting (T5), rice-bean rotation under wet direct seeding (T6), rice-rice-bean rotation under dry direct seeding (T7), and rice-rice-bean rotation under no-till (T8). Data on yields, incomes, and production costs were collected and utilized to calculate the system rice equivalent yield, system productivity efficiency, water use efficiency, and system net benefit. The rice-rice-bean rotation under transplanting exhibited the highest values system rice equivalent yield, productivity efficiency, water use efficiency, and net benefit, which were 157%, 13%, 66%, and 184% higher than those of the rice cultivation once-a-year, respectively. The study suggests that the rice-rice-bean rotation under transplanting could be recommended to producers to improve yield, benefits of rice systems in lowlands.